Is incident rheumatoid arthritis interstitial lung disease associated with methotrexate treatment? Results from a multivariate analysis in the ERAS and ERAN inception cohorts. Issue 5 (5th May 2019) - Kiely, Patrick; Busby, A D; Nikiphorou, E; Sullivan, K; Walsh, D A; Creamer, P; Dixey, J; Young, A
Abstract : Objectives: To assess predictive factors for rheumatoid arthritis interstitial lung disease (RA-ILD) in two early rheumatoid arthritis (RA) inception cohorts with a focus on methotrexate (MTX) exposure. Design: Multicentre prospective early RA inception cohort studies; the early RA study (ERAS) and the early RA network (ERAN). Setting: Secondary care, ERAS nine centres, ERAN 23 centres in England, Wales and Ireland. Participants: Patients with new diagnosis of RA, n=2701. Standardised data including demographics, drug therapies and clinical outcomes including the presence of RA-ILD were collected at baseline, within 3–6 months, at 12 months and annually thereafter. Primary and secondary outcome measures: Primary outcome was the association of MTX exposure on RA-ILD diagnosis. Secondary outcomes were the association of demographic, comorbid and RA-specific factors on RA-ILD diagnosis and the association of MTX exposure on time to RA-ILD diagnosis. Results: Of 92 eligible ILD cases, 39 occurred in 1578 (2.5%) MTX exposed and 53 in 1114 (4.8%) non-MTX exposed cases. The primary analysis of RA-ILD cases only developing after any conventional synthetic disease-modifying antirheumatic drug treatment (n=67) showed MTX exposure not to be associated with incident RA-ILD (OR 0.85,  95% CI 0.49 to 1.49, p=0.578) and a non-significant trend for delayed ILD diagnosis (OR 0.54,  95% CI 0.28 to 1.06, p=0.072). In an extended analysis including RA-ILD cases present at RA diagnosis (n=92), MTX exposure was associated with a significantly reduced risk of incident RA-ILD (OR 0.48, 95% CI 0.3 to 0.79, p=0.004) and longer time to ILD diagnosis (OR 0.41, 95% CI 0.23 to 0.75, p=0.004). Other independent baseline associations with incident RA-ILD were higher age of RA onset, ever smoking, male gender, rheumatoid nodules and longer time from first RA symptom to first outpatient visit. Conclusions: MTX treatment was not associated with an increased risk of RA-ILD diagnosis. On the contrary, evidence suggested that MTX may delay the onset of ILD.